PERANAN METODE PEMBELAJARAN TERHADAP MINAT DAN PRESTASI BELAJAR PESERTA DIDIK - Almaydza Pratama Abnisa (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2021)
Learning as a process is designed by educators to create a variety of innovative students so as to increase expertise in knowledge, and build good mastery of learning materials. Implementation in learning as the basis for formal learning in which there is communication between the various components of learning. The various components are divided into several categories including the following: the presence of educators, learning materials, and the presence of students. These components will require others such as the existence of media, methods, facilities and infrastructure, the management of the learning implementation environment, thus the conditions for the implementation of learning can be formed so as to achieve the target of learning. Learning is the key for each individual to produce knowledge.